Analisis Keselamatan dan Kesehatan Kerja Menggunakan Metode Hazard Identification And Risk Assessment Pada Proyek Konstruksi - Yusra Aulia Sari; I Wayan Yoga Baskara; I Nengah Riana; Komang Agus Ariana (Universitas Pendidikan Nasional, 2022)
The construction service sector is one of the many business fields that are classified as very prone to accidents. This research takes a case study, namely the Bali Kura-Kura Creative Campus Development Project which requires a lot of human resources and is of course prone to construction accidents due to negligence or human error. The purpose of this study is to determine the level of accident risk that occurs and provide K3 recommendations after knowing the level of accident risk. In this study the questionnaire was used as a data collection tool. Questionnaires were compiled from predetermined research variables. After knowing the variables and data, the next step is to apply the Hazard Identification and Risk Assessment (HIRA) method The conclusion that can be drawn from this research is the calculation using the HIRA method, which is that there are activities with a low risk level of 3 (15%) sources in the excavation area. Then there are 5 sources (25%) that are included in the medium risk level and 10 sources (50%) of the risk that are included in the high risk category found in all activity areas. Meanwhile, in the extreme risk category, there are 2 sources (10%) found in the excavation area and based on the analysis, it can be seen that the recommendations for improvement proposals that can be made include tightening supervision on each worker activity, enforcing SOPs for each activity, providing safety signs on certain areas that may pose a potential hazard, provide personal protective equipment (PPE).